Current and future opportunities for the management of primary biliary cholangitis - Naffouj, Sandra; Wang, Jennifer (Frontiers in Gastroenterology, 2023)
Primary biliary cholangitis (PBC) is a rare immune-mediated chronic cholestatic liver disease that can progress to liver fibrosis and, ultimately, cirrhosis if left untreated. Since the pathogenesis of PBC is not well understood, curative therapies have yet to be established. Ursodeoxycholic acid (UDCA), the standard of care treatment for PBC, has been proven to reduce disease progression and improve transplant-free survival. However, one third of patients have no response or partial biochemical response to UDCA and are at increased risk for disease progression. In such cases, second-line therapy with obeticholic acid (OCA) or peroxisomes proliferator-activated receptors (PPARs) should be considered in conjunction with UDCA. In this review article, we aim to provide an overview of the most recent data on PBC treatment in patients with inadequate response to UDCA, as well as novel therapies in the early stages of development.